Comparison of 3 Postthrombotic Syndrome Assessment Scales Demonstrates Significant Variability in Children and Adolescents With Deep Vein Thrombosis. Issue 8 (November 2015) - Raffini, Leslie; Davenport, Jillian; Bevilacqua, Lisa; Iosifescu, Sarah
Abstract : Postthrombotic syndrome (PTS) is an important outcome in children with deep vein thrombosis (DVT). There are several instruments to measure PTS, and no accepted "gold standard." The objective of this cross-sectional prospective study was to compare the prevalence of PTS in patients above 8 years old with a history of DVT using 3 scales: the Villalta scale, a pediatric modification of the Villalta scale, and the Manco-Johnson instrument. Forty-four subjects (22 females) were enrolled; mean age 16.6 years (SD 3.6 y). The majority had a lower extremity DVT. The average duration from DVT to PTS assessment was 2.6 years. The proportion of subjects with PTS using the adult Villalta scale was 11%, which was significantly less than the 66% of patients identified using both pediatric scales ( P <0.0001). The majority of patients with PTS as determined by the pediatric scales had mild PTS. There was significant discordance between the prevalence of PTS using the Villalta scale compared with the 2 pediatric scales. This is especially relevant when considering which instrument to use in adolescent patients. This study demonstrates that PTS, as defined by these scales, is not a well-defined or standardized outcome, particularly when comparing adult and pediatric instruments.